2020
DOI: 10.1080/10549811.2020.1771376
|View full text |Cite
|
Sign up to set email alerts
|

Forest Management Approaches for Climate Change Mitigation and Adaptation: a Comparison Between Germany and Japan

Abstract: Forest management affects carbon sequestration (mitigation) and resilience of forest ecosystems (adaptation) under climate change. Therefore, the efforts to integrate these two approaches have been made by the political arrangements to seek the synergy effects and deal with trade-offs. To study the state of the art linkages and forest policies to realize both adaptation and mitigation, we systematically review the literature highlighting the topic (136 publications) and outline two different approaches from Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
(113 reference statements)
0
2
0
1
Order By: Relevance
“…1). К слову об изменении климата и лесохозяйственной деятельности, можно отметить, что несколько статей посвящены оценке экосистемных функций лесов в целом, в том числе вопросам лесоклиматических проектов [42][43][44][45].…”
Section: результатыunclassified
“…1). К слову об изменении климата и лесохозяйственной деятельности, можно отметить, что несколько статей посвящены оценке экосистемных функций лесов в целом, в том числе вопросам лесоклиматических проектов [42][43][44][45].…”
Section: результатыunclassified
“…Through empirical analysis, Xu et al found that cross-sectoral climate policy is more conducive to achieving the goal of increasing forest carbon sinks by implementing multiple strategies rather than only a single strategy [ 45 ]. Moreover, cross-sectoral climate policies not only reap the benefits of reduced carbon emissions but also promote carbon emissions and carbon sequestration to offset each other [ 46 ]. It can be seen that a cross-sectoral climate policy can not only promote the increase of forest carbon sinks but also reduce the cost of climate policies.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…The CFOMP has a core action plan on CC and recognises groups' contribution to strengthening local livelihoods and diversifying income sources(Mishra et al, 2019).Authorised forest professionals, including the Divisional Forest O cer (DFO), national and state government authorities monitor and evaluate the plan's activities.2.2 Mitigation strategy for CCBiophysical interactions between mixed tree species with an active silvicultural management plan play a vital role in the mitigation strategy for CC. Open discussions with local stakeholders, forestry professionals, and political leaders at national, state, and local level are required to develop and implement the CFOMP with a clear aim of CC mitigation(Yousefpour et al, 2020). Cross-sector coordination, stakeholders' integration, democratic decision-making and enhancing forestry professionals' capacity assist the mitigation strategies with nancial resources (Ahmed et al, 2019).3.…”
mentioning
confidence: 99%